2019
DOI: 10.1142/s0192415x19500149
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychological Health Outcomes of Qigong Exercise in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Physical limitations, depression and anxiety are prevalent among older adults. Mild to moderate exercise can promote physical and psychological health and reduce the risk of chronic diseases. Qigong, a type of Chinese traditional medicine exercise, has demonstrated beneficial effects on physical ability and mental health in adults with chronic conditions. The purpose of this review was to systematically assess the effects of Qigong exercise on physical and psychological health outcomes in older adults. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 38 publications
1
40
1
1
Order By: Relevance
“…In the latter case, perhaps even larger effects may be observed in terms of psychological health outcomes, since a predominant tendency towards improvement of the examined outcomes was demonstrated in older adults without mental disorders by the present work. This implies the necessity of perceiving MBI involving meditative movements as a future research topic to further confirm these types of exercise as a potential cost-effective, non-pharmacological, preventive method for counteracting the increase of mental disorders among older adults [ 4 ]. These interventions may offer an age-appropriate possibility of improving psychological health through various levels and simultaneously incorporating more movement into daily life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the latter case, perhaps even larger effects may be observed in terms of psychological health outcomes, since a predominant tendency towards improvement of the examined outcomes was demonstrated in older adults without mental disorders by the present work. This implies the necessity of perceiving MBI involving meditative movements as a future research topic to further confirm these types of exercise as a potential cost-effective, non-pharmacological, preventive method for counteracting the increase of mental disorders among older adults [ 4 ]. These interventions may offer an age-appropriate possibility of improving psychological health through various levels and simultaneously incorporating more movement into daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological outcomes can be improved by regular physical activity and exercise in adults of all ages [ 3 ]. The fact that psychological symptoms are commonly experienced in later life reveals a need for age-appropriate exercise programs as preventive measures that do not only address physical but also psychological health in older people [ 4 , 5 ]. A potential approach is offered by alternative forms of exercise (e.g., mind–body interventions (MBI)) with low impact, low demands on the muscles and less energy expenditure [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of mind includes focusing attention and visualization. Most operations of mind regulation are similar to meditation, [ 29 31 ] which can produce a relaxation response and stress reduction. TCE is often used in the prevention and treatment of respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the intervention effect of physical and mental exercises on the mental health of the middle-aged and old people has received attention from the scienti c circle, and meta-analysis has shown that physical and mental exercises are effective in adjusting the mental health of the middle-aged and old people [19][20][21][22][23][24]. However, in these meta-analysis, two scales of depression or anxiety were used to measure mental health, and no SCL-90 scale was used to measure mental health.…”
Section: Introductionmentioning
confidence: 99%